Edukasi Ketrampilan, Minat dan Bakat untuk Meningkatkan Perekonomian Generasi Bangsa di Pondok Pesantren Baitul Quro - Tohiroh Tohiroh; Adhy Firdaus; Joned Ceilandra Saksana; Firmansyah Firmansyah; Putri Noor Ramayanti; Cinta Rahmi; M. Tafsiruddin; Syarif Hidayatullah; Rasmawati AR; Moh. Tahang; Aep Saefullah; Hilda Fariha; Khoirul Anam; M. Islah (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2021)
This community service aims to identify and develop the skills, interests, and talents of students at the Baitul Quro Islamic Boarding School as an effort to improve the economy of the nation's generation. This activity was held in May 2020. The methods used in this study include an initial survey to identify the interests and talents of students, skills training relevant to the survey results, and periodic evaluations to measure the development and effectiveness of the program. The training provided includes entrepreneurial skills, information technology, handicrafts, and creative arts. The results of the activity showed a significant increase in the skills and abilities of students which was measured through an increase in practical exam scores and individual projects. The implication of this activity is to increase the ability of students to create independent business opportunities that contribute positively to the local economy. The success of this program shows that skills education that suits individual interests and talents can be one of the effective solutions in improving the economic welfare of the community.